2013
DOI: 10.1186/1472-6963-13-278
|View full text |Cite
|
Sign up to set email alerts
|

The association of smoking status with healthcare utilisation, productivity loss and resulting costs: results from the population-based KORA F4 study

Abstract: BackgroundSmoking is seen as the most important single risk to health today, and is responsible for a high financial burden on healthcare systems and society. This population-based cross-sectional study compares healthcare utilisation, direct medical costs, and costs of productivity losses for different smoking groups: current smokers, former smokers, and never smokers.MethodsUsing a bottom-up approach, data were taken from the German KORA F4 study (2006/2008) on self-reported healthcare utilisation and work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 37 publications
3
55
0
6
Order By: Relevance
“…[4,[12][13][14][15] Another study in a developed country also found that current smokers were more likely to be hospitalized compared to nonsmokers. In addition, current smokers were more likely to have frequent outpatient visits compared to nonsmokers.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…[4,[12][13][14][15] Another study in a developed country also found that current smokers were more likely to be hospitalized compared to nonsmokers. In addition, current smokers were more likely to have frequent outpatient visits compared to nonsmokers.…”
Section: Discussionmentioning
confidence: 92%
“…[1,2] It accounts for more than 5 million deaths annually and imposes both health and financial burdens on individuals, health systems, and society as a whole. [3,4] In Iran, the prevalence of smoking is about 12.5% (of which 23.4% males and 1.4% females) and on average an individual used to smoke 13.7 cigarettes daily. [5] A study in Iran in 2012 indicated that smoking is accountable for 4623 cancer deaths, 80,808 years of potential life lost, and $US 83,019,583 cost of productivity losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In England, Germany, Hungary and Spain data on the number of days lost per smoker came from the published sources 56, 57, 58, 59, whereas in the Netherlands, reports on health‐care figures were available to derive the number of lost work‐days 60. Average hourly wage was obtained in all cases through search and analysis of national databases 61, 62, 63, 64.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to males, the mortality rate of lung cancer in females has been rising in Germany for more than three decades, with smoking as the biggest risk factor 6, 7. Using survey data, health‐related costs of smoking in Germany have been estimated to amount to more than €30 billion per year 8. Thus, tobacco control remains a fundamental leverage point to improve population health outcomes 9.…”
Section: Introductionmentioning
confidence: 99%